Institutional capacity of local municipalities in the delivery of services to communities : a case study of the Polokwane Municipality in Limpopo Province - Chipu, Sello Tlou Levy (My University, 2011)
A large percentage of the national budget goes to municipalities to provide services to communities. Since 2000, National Treasury has been increasing the budget to municipalities to enable them to deliver better quality services and to expand the provision of basic amenities. Despite this huge financial investment, there is still poor access and use of social and infrastructure services by most communities in South Africa. The primary aim of this study is to investigate the institutional capacity of municipalities in delivering services to communities: a case study of the Polokwane Municipality in Limpopo. This case study used various data-collecting methods such as interviews, documentation and archival records to come to a conclusion. An interview schedule was used in this study to allow the key respondents to give more detailed information about the problems or challenges facing the municipality in delivering services. The study concluded that the Polokwane Municipality has the necessary institutional capacity to deliver on its constitutional mandate. However, there are specific capacity challenges that need to be addressed.
Thesis (M. Dev.) --University of Limpopo, 2011
Keywords: Municipalities; Local government; Municipal government -- South Africa -- Limpopo; Municipal services -- South Africa -- Limpopo